The bitumen batching system's modernization and its effective analysis at the asphalt mixing plant - Bražiūnas, Justas; Sivilevičius, Henrikas (Transport, 2010)
Some particular aspects such as the improvement methods of technological parameters for hot bitu‐ men storage in a pipeline transport system, transportation and dosed supply to batch asphalt mixing plant (AMP) are evaluated in this paper. Bitumen in asphalt concrete binds together the material of mineral particles into a strong conglomerate of a complicated structure, capable of withstanding the destructive effect of vehicles and the factors on the road pavements. The optimal amount of bitumen determined by calculation and laboratory testing should be maintained in mix batches of hot‐mix asphalt (HMA) obtained from AMP mixer. In the periodic type of the asphalt concrete blender mass of the weighted matrix in the all merging batcher's tanks should correspond in percents equally in the HMA to the designed amount of the job‐mix formula (JMF). The bitumen batcher does not always weigh bitumen portions precisely. Their mass deviations from the amount determined by JMF and its variation impair HMA composition and performance. In addition,, an additive model for calculating the effect of factors causing the variance of bitumen content in the produced HMA mixture is presented in this current paper as well. The data on statistical evaluation of bitumen batcher's modernization performed at certain Lithuanian Enterprise are discussed. The differences in structures of reconstructed and not reconstructed bitumen batching systems (BBS) are analysed and methods of determining modernization effectiveness are presented. The effectiveness of BBS is analysed too, defining the deviations of bitumen content in subsamples, taken and extracted everyday for two seasons (before and after the batcher's modernization) of HMA mixture production from the value of JMF and comparing them to the values of tolerances. The analysis of column charts and histograms shows that the made modernization helped to increase the precision of supplying the required amount of bitumen to HMA mixture insignificantly. However, the control of BBS has been considerably increased.First published online: 10 Feb 2011